ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN FRAILTY SYNDROME PADA LANSIA WANITA DI WILAYAH KERJA PUSKESMAS SINGOSARI - Siti Nuryatul Badriyah; Tri Nataliswati; Tri Cahyo Sepdianto; Sumirah Budi Pertami (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Elderly is someone who is in the final stage of adulthood where age starts from 60 years and over. This condition is interpreted as a decrease, weakness, increased risk of various diseases and other physiological changes. Elderly who experience this condition is called frailty syndrome. If not handled properly frailty syndrome can lead to increased death in the elderly. This study used a quantitative design with a cross sectional approach and data collection was carried out using a questionnaire as an instrument. The independent variables in this study were sociodemographic (abandonment and family functioning), physical, nutritional, psychological, functional and cognitive. While the dependent variable is frailty syndrome. The research sample was 95 respondents using purposive sampling technique. The analytical method uses the Spearman Rank test. Factors related to frailty syndrome at the Singosari Health Center were sociodemographic factors (neglect) (p=0.000), physical factors (p=0.000), functional factors (p=0.000), psychological factors (p=0.000), cognitive factors (p=0.000) and nutritional factors (p=0.000), while sociodemographic factors (family functions) (p=0.214) had no relationship with frailty syndrome and the most dominant factor was functional factors. The suggestion put forward is that the health center increases the intensity of physical exercise programs that already exist at the puskesmas and at the elderly Posyandu such as walking together and exercising for the elderly and inviting the elderly to participate actively in order to increase independence.